The Influence of a Realistic Mathematics Education Approach on Students' Mathematical Problem Solving Ability - Fitriana, Hanny; Waswa, Anne N. (Interval: Indonesian Journal of Mathematical Education, 2024)
Purpose of the study: The purpose of this research is to determine the effect of a realistic mathematics education approach on students' mathematical problem solving abilities. Methodology: The method used was a quasi-experiment with a post-test only research design. Sampling was carried out using the cluster random sampling technique. The research instrument given was a test with a description type of 5 questions. Data analysis using the t-test from both groups obtained a t value of 4.47 , while t table was at a significance level of 5% with degrees of freedom (dk) = 47.09, namely 1.68, so it can be said that t count > t table. Main Findings: the results of hypothesis testing using the "t test" for heterogeneous samples obtained t = 4.47 and t table = 1.68, with a significance level of α = 5% and degrees of freedom (dk) = 47.09. This data shows that H 0 is rejected and H 1 is accepted or in other words the mathematical problem solving ability of students in the experimental group is higher than the mathematical problem solving ability of students in the control group. Novelty/Originality of this study: Research on the effect of the Realistic Mathematics Education approach on students' mathematical problem solving abilities shows significant improvements in students' analytical and applied skills, opening new avenues for more effective teaching methods in schools. Apart from that, this approach not only improves mathematical abilities but also enriches students' learning experiences through a more real and relevant context.